PENGARUH PENERAPAN BELAJAR MANDIRI PADA MATERI EKOSISTEM TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN KEMAMPUAN MEMECAHKAN MASALAH SISWA SMA DI KOTA METRO - Anak Agung Oka (UNIVERSITAS MUHAMMADIYAH METRO, 2010)
The objective of this research was to know the effect of alone learning to the critical thinking skill and problem solving ability in SMA Teladan 1 Metro. This research applied quasy experimental with non-equvalent control group design. The population of this research is allow students of class X SMA Teladan 1 Metro on academic year 2009/2010. The samples of this research were class XA as experimental (alone learning) and class XB as control (conventional). The instrument of this research namely critical thinking and problem solving test. This research data are quantitative data consisted by score capacity critical thinking and problem solving ability to river ecosystem, collected on 15 january until 12 Juni 2010. Data were analysed by bilinear covariant statistical analysis (Ancova), continued with LSD test. The result of this research indicated that there were an effect of alone learning strategy toward the critical thinking skill and problem solving ability. Student with alone learning strategy having critical thinking higher 80,111% than conventional learning. Beside, student with alone learning strategy having 11,124% higher than convensional learning. Based on this research, the researcher suggest to the teacher that this strategy can implemented in biology learning. Kata Kunci: Belajar Mandiri, Keterampilan Berpikir Kritis, Kemampuan Memecahkan Masalah.